Carboxymethylchitosan, alginate and tulle gauze wound dressings: A comparative study in the treatment of partial-thickness wounds - Angspatt,A. (IOS Press, 2015)
Background: Carboxymethylchitosan is a chitosan-derivative obtained from the carboxymethylation of chitin with chloroacetic acid in alkaline solution. It has shown its potential in animal model studies as an accelerator of wound healing. Materials and methods: Prospective, comparative clinical trials of traditional tulle gauze, alginate membrane, and carboxymethylchitosan sponge were carried out in the treatment of partial-thickness skin graft donor sites. Between June 2005 and March 2006, 70 donor sites from 44 patients were randomly treated by these three different wound dressing materials. Each wound was treated until it was completely healed, and a visual analogue scale was used for the pain evaluation. Results: The results showed that the donor sites dressed with carboxymethylchitosan or alginate healed more rapidly than those treated with tulle gauze. There was no significant difference in the healing rate between carboxymethylchitosan and alginate. The pain scores evaluated among these three dressing groups did not significantly differ. Conclusion: Carboxymethylchitosan is as efficacious as traditional tulle gauze or alginate membrain in the treatment of partial thickness skin graft donor sites.